Frequency and its Associated Factors of Proteinuria Among Women having Preeclampsia with Hypertensive Disorders in Pregnancy at Khyber Teaching Hospital (KTH) Peshawar - Ambareen, Asma; Mazhar, Tayyaba; Ateeq Ur Rehman,; Nosheen, Sania; Hussain, Farid (Indus Journal of Bioscience Research, 2025)
Background: Hypertensive disorders during pregnancy pose substantial risks to both maternal and fetal health. Preeclampsia, characterized by new-onset hypertension and proteinuria, represents a significant global health concern with varying regional prevalence. Objective: This study aims to address the critical knowledge gap regarding the frequency and associated factors of proteinuria among women with Preeclampsia and Hypertensive Disorders in Pregnancy. Materials and Methods: In this cross sectional study, the gestational age was determined by either dates or first-trimester scans. Blood pressure measurements were taken, and Preeclampsia was diagnosed using established criteria. Urine samples were collected and analyzed for proteinuria. Patients were further screened for systemic lupus erythematosus and diabetes mellitus. Exclusion criteria included multiple pregnancies, chronic hypertension, renal disease, and chronic diabetes mellitus. Data were analyzed using SPSS version 22, and statistical significance was set at p ≤ 0.05. Results: Of the 137 participants, 54 (39.4%) were primiparous, and 83 (60.6%) were multiparous. The average age was 31.26 years with a range of 17-45 years. Proteinuria was detected in 26 (18.98%) patients. Proteinuria prevalence did not significantly vary by age group. However, its occurrence was notably higher in severe hypertensive patients (46.2%) and those with comorbidities such as diabetes (58.1%) and systemic lupus erythematosus (100%). Parity did not emerge as a decisive factor. Conclusion: Approximately 19% of the studied participants exhibited proteinuria, emphasizing the need for vigilant management and targeted interventions for high-risk pregnancies. While age showed limited influence, the severity of hypertension strongly correlated with proteinuria. Comorbidities, especially diabetes and systemic lupus erythematosus, significantly elevated the risk. Parity, however, did not emerge as a decisive factor.